2010
DOI: 10.1158/0008-5472.can-09-4417
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Incidence Trends in the United States and United Kingdom: Evidence of Right- to Left-Sided Biological Gradients with Implications for Screening

Abstract: Several lines of evidence support the premise that screening colonoscopy reduces colorectal cancer (CRC) incidence, but there may be differential benefits for right-and left-sided tumors. To better understand the biological basis of this differential effect, we derived biomathematical models of CRC incidence trends in U.S. and U.K. populations, representing relatively high-and low-prevalence screening, respectively. Using the Surveillance Epidemiology and End Results (SEER) and the Office for National Statisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 45 publications
5
97
0
Order By: Relevance
“…This difference in the influence of gender on the regional distribution of adenomas in our patient group, as compared to the distribution of cancers, may be related to gender differences in the biological behavior of the mucosa of the right and left colon. 30 With increasing life expectancy, especially in women, and with improving health of aging people, the future age limits for colonoscopy screening 31 may have to be reconsidered. We suggest that the reported left-to-right shift of colonic adenomas 19,20 is partly due to recent improvements in the detection of right colonic adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in the influence of gender on the regional distribution of adenomas in our patient group, as compared to the distribution of cancers, may be related to gender differences in the biological behavior of the mucosa of the right and left colon. 30 With increasing life expectancy, especially in women, and with improving health of aging people, the future age limits for colonoscopy screening 31 may have to be reconsidered. We suggest that the reported left-to-right shift of colonic adenomas 19,20 is partly due to recent improvements in the detection of right colonic adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…This process is best illustrated for colorectal cancer-the total period from first initiated cell to clinical cancer presentation is termed the sojourn time and is approximately 50 years [54], whereas the period from the first clinically identifiable adenoma (only a few millimetres in size) to incident cancer is approximately 20 years, and the period from a clinically relevant adenoma (i.e. larger high-risk lesion) to cancer presentation is approximately 7 years.…”
Section: Tumorigenesis Latency Periods and Natural History Of Type 2mentioning
confidence: 99%
“…A fully functional ADA, facilitating the irreversible degradation and removal of adenosine, may be necessary in the setting of increased purine and pyrimidine metabolism in carcinogenesis. Previous studies have observed higher levels of ADA activity in cancerous colorectal tissue, as compared with normal adjacent tissue from the same subjects, and in cancerous bladder tissue, as compared with normal adjacent tissue from the same subjects and from cancer-free subjects (34,37 proliferation (39), and its gene product is a useful prognostic marker for certain types of cancer (40,41). CDO1 catalyzes the production of cysteine sulfinate from cysteine, which is metabolized from homocysteine and serine.…”
Section: Discussionmentioning
confidence: 99%